Colitis Cystica Profunda Mimicking Malignancy - Sheenam Azad; Brijesh Thakur; Seema Acharya; Shefali Kamboj; Rajiv Kumar Azad (Indian Journal of Medical Specialities)
Colitis cystica profunda (CCP) is nonneoplastic lesion characterised by the presence of intramural mucosal herniation or mucus-containing cysts in the colon and rectum. <200 cases have been reported in the English literature searched to the best of our knowledge. The cause of the lesion is not clear and a confident diagnosis can be made only on histopathology. We present a series of three cases with clinical and/or radiological possibility of colonic neoplastic etiology. These cases include two females of 32 and 76 years of age, respectively, and a 51-year-old male patient presented with nonspecific symptoms (loss of weight/appetite, episode of blood-mixed stools, pain in abdomen, constipation, and burning micturition). Rescected colonic segments were sent for histological examination, and the final histopathological diagnosis of all three cases was CCP. CCP is a rare benign condition that may mimic carcinoma clinically and grossly at times. The surgeon and pathologist must be aware of this entity to avoid radical treatment.